Propriedades ópticas e elétricas de materiais híbridos de sílica/orgânico à base de GPTS:TEOS preparados pelo método sol-gel - Quadros, Matheus Henrique [UNESP] (2015)
Fabrication of optoelectronic devices requires the employment of at least one transparent electrode. Usually, commercially transparent electrodes have been made by deposition of indium tin oxide (ITO) films by RF-Sputtering technique. These commercial electrodes have sheet resistance of about 100 Ω/sq and optical transmittance of 77% at the wavelength of 550 nm. The poly(3,4-ethylenedioxythiophene):polystyrene-sulfonate (PEDOT:PSS) is an alternative material to fabricate transparent electrodes due to its high conductivity (about 600 S/cm) and solubility in water. Soluble conductive materials exhibits advantages for processing of electrode layers, however there is a disadvantage during devices fabrication once materials with the same solvent of the electrode material cannot be coated one over the other. Alternatively, organic/Silica hybrid materials prepared by sol-gel process allow producing bulks and films with high chemical durability. In order to obtain transparent electrodes with high chemical durability, we introduced a blended material comprising the high UV-VIS transparency of organic/Silica sol-gel material and a high conductivity polymer PEDOT:PSS. The organic/Silica sol was obtained using two different molar concentrations (1:1 and 4:1), of tetraethylorthosilicate (TEOS) and 3-glycidoxypropyltrimethoxysilane (GPTS). Amounts of PEDOT:PSS solutions were added to the sol material, resulting in different weight fractions of sol and polymer. G:T/P:P were deposit onto glass substrates by spray-coating. In order to perform electrical characterization of the blended material, gold electrodes were thermally evaporated onto the films. The electrical characterization was performed using a Keithley 2410 source/meter unity and the optical characterization, using a Cary50 UV-Vis spectrophotometer. The absorption coefficient and electric conductivity of the different compositions blends, as function of the PEDOT:PSS concentration, were...